Economic Impact of the Olmeca Refinery in the municipality of Paraiso, Tabasco (Revista de Investigaciones Universidad del Quindío, 2022)
This research aims to investigate how the economic impact of the Olmeca refinery occurs in the municipality of Paraíso, Tabasco and understand the importance of refineries to be able to process crude oil so that it can be converted into gasoline, gas and oil, being the most important fuels due to the use that is given to it in our daily lives, remembering that oil is not only used for those three products mentioned above, but it is also used for the production of plastics, polyethylene, heating and a host of other products. Documentary research, searching Google Scholar, Science Direct, Research Gate, Scie ELO, on the official website of the Mexican government and renowned newspapers such as Milenio, El Financiero, finding more than 18 articles that supported the development of this research.
Keywords: Refinery; economic impact; petroleum; extraction; production; oilfields